Vitamin C, doxycycline, and azithromycin (VDA) targeted changes in cellular senescence-related genes in human adipose-derived mesenchymal stem cells - Roshanak Alvandi; Samira Salimiyan; Mohammad Moradzad; Mobin Mohammadi; Shohreh Fakhari; Mohammad Rahmani (Iranian Journal of Basic Medical Sciences, 2024)
Objective(s): Adipose-derived Mesenchymal stem cells (ASCs) have garnered attention for their regenerative potential; therefore, their cellular senescence-related gene expression remains crucial in therapeutic contexts. Nowadays, combination therapies have shown promising results in reducing senescent cells. This study investigated the effects of vitamin C, doxycycline, and azithromycin co-treatment on the key cellular senescence-associated genes in ASCs.Materials and Methods: Human ASCs were cultured and treated for 24 hr with vitamin C, doxycycline, azithromycin, and a combination of three drugs. Total RNAs were extracted, and the expression of p21, p16, Nanog, Oct4, and Sox2 genes was assessed using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Additionally, cell cycle alterations were analyzed via flow cytometry after treatment with these compounds. Results: Notably, vitamin C treatment resulted in a significant down-regulation of p21 gene expression (P<0.01), implicating the potential role of vitamin C in promoting cell cycle progression. Doxycycline treatment led to a significant up-regulation of p21 and p16 gene expression (P<0.05), as it has previously been shown to induce cell cycle arrest. Similarly, azithromycin treatment predominantly increased p21 expression (P<0.05). Besides, cell cycle analysis revealed that each compound had changed the distribution of cells across different phases of the cell cycle. Conclusion: The combined use of all three drugs yielded intricate interactions, suggesting a complex yet promising approach to future research. According to our findings, the major difference in the combination drug-treated group (VDA) can be explained by the neutralizing effect of these three components in the environment.